Wealth-income ratios in a small, developing economy: Sweden, 1810-2014 - Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2016)
This study uses new data on Swedish national wealth over the last two hundred years to examine whether the patterns in wealth-income ratios found by Piketty and Zucman (2014) extend to small and less developed economies. The findings reveal both similarities and differences. During the industrialization era, Sweden's domestic wealth was relatively low because of low saving rates and instead foreign capital imports became important. Twentieth century trends and levels are more similar, but in Sweden government wealth grew more important, not least through its relatively large public pension system. Overall, the findings suggest that initial conditions and economic and political institutions matter for the structure and evolution of national wealth.
Keywords: D30; E01; E02; N30; 330; National wealth; Household portfolios; Pension wealth; Welfare state; Institutions; Economic history